Successful treatment of superficial basal cell carcinoma in the central face by photodynamic therapy in an Asian woman with dermoscopic diagnosis and a serial follow-up - Ya-Wen Hsiao; Fang-Wen Tseng; Chih-Hsun Yang; Cheng-Sheng Chiu (Wolters Kluwer Medknow Publications, 2011)
Superficial basal cell carcinoma and tinea nigra sometimes share similar clinical manifestations. Herein, we report the case of a 56-year-old Asian woman with superficial basal cell carcinoma located on her philtrum, which was initially misdiagnosed as tinea nigra. We also describe the different distinguishing features of this lesion under dermoscopic examination to improve the diagnostic accuracy. Because of the relatively low rate of metastasis and less aggressive nature of a superficial basal cell carcinoma, cosmetic concerns should be taken into consideration in planning treatment. In this case, the patient received photodynamic therapy that yielded an excellent clinical response over a 9-months follow-up.